HLA-C Alleles and Cytomegalovirus Retinitis in Brazilian Patients with AIDS - Tânia Gisela Biberg-Salum; Maria de Lourdes Veronese Rodrigues; Ana Paula Morais Fernandes; Neifi Hassan Salum Deghaide; Jayter Silva de Paula; Erick C. Castelli; Celso Teixeira Mendes-Junior; Eduardo Antonio Donadi (Journal of Ophthalmology)
Purpose. Since cytomegalovirus retinitis (CR) is an important cause of visual impairment among AIDS patients and HLA-C alleles have been associated with AIDS disease outcome, we typed HLA-C locus in patients with AIDS exhibiting or not CR. Methods. Three groups of individuals were studied: (i) 49 patients with AIDS and CR (Group I), (ii) 161 patients with AIDS without CR (Group II), and (iii) 202 healthy HIV-negative individuals (Group III). HLA-C typing was performed using commercial kits. Results. The HLA-C∗07 allele group was underrepresented in AIDS patients with CR (P=0.005) when compared to controls or when compared to AIDS patients without CR (P=0.006). The HLA-C∗05 allele group was overrepresented in Group II in comparison to Group III (P=0.017). The frequency of the HLA-C∗16 allele group was increased in Group III in comparison to Group II (P=0.004). Conclusion. The HLA-C∗07 allele group conferred protection against the development of CR in Brazilian AIDS patients, whereas the HLA-C∗05 and HLA-C∗16 allele groups were associated with AIDS susceptibility or protection, respectively.